Glioblastomas with Oligodendroglial Component – Common Origin of the Different Histological Parts and Genetic Subclassification - Barbara Klink; Ben Schlingelhof; Martin Klink; Karen Stout-Weider; Stephan Patt; Evelin Schrock (Analytical Cellular Pathology)
Background: Glioblastomas are the most common and most malignant brain tumors in adults. A small subgroup of glioblastomas contains areas with histological features of oligodendroglial differentiation (GBMO). Our objective was to genetically characterize the oligodendroglial and the astrocytic parts of GBMOs and correlate morphologic and genetic features with clinical data.